A influência da ausência paterna no desenvolvimento emocional do filho: responsabilidade civil por abandono afetivo - Pereira, Lucas Henrique Ramos (Universidade Federal do Tocantins, 2023)
The present undergraduate thesis aims to investigate the implications of paternal absence on the emotional development of children and the possibility of civil liability arising from emotional abandonment. The research examines the changes in contemporary family structures, the effects of paternal absence on the emotional development of children, and the principles that guide family law, such as human dignity, affection, and responsible parenthood. Additionally, the study examines the issues related to civil responsibility in the context of emotional abandonment. The methodology adopted is exploratory, based on a literature review of scientific articles, legal doctrines, and jurisprudential analysis. After analyzing the problem and studying doctrinal and jurisprudential perspectives, it was verified that civil liability can be applied to compensate for the damages resulting from emotional abandonment in parent-child relationships